Adsorbent

The use of an amorphous magnesium silicate compound with low alkali metal content and high solid acidity as an adsorbent addresses the issue of excessive waste in polyether polyol purification by enhancing adsorption capacity and reducing the amount of adsorbent required.

JP2025071257AActive Publication Date: 2025-05-02SETOLAS HLDG INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2025026179
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2025-02-20
Publication Date
2025-05-02
Estimated Expiration
2043-07-13

AI Technical Summary

Technical Problem

Conventional adsorbents require a large amount for alkali metal-containing basic catalysts, leading to excessive waste generation during the purification of polyether polyols.

Method used

An amorphous magnesium silicate compound with low alkali metal content and high solid acidity is used as an adsorbent, enhancing its adsorption capacity and reducing the amount needed.

Benefits of technology

The novel adsorbent achieves a high adsorption capacity, allowing for efficient removal of alkali metal-containing catalysts with a significantly reduced amount of adsorbent, thereby minimizing waste and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025071257000001_ABST
    Figure 2025071257000001_ABST
Patent Text Reader

Abstract

To provide a novel adsorbent that has a high adsorption capacity and that is capable of adsorbing a target material with a small amount of use.SOLUTION: The present disclosure provides an adsorbent composed of an amorphous magnesium silicate compound. The magnesium silicate compound according to the present disclosure has an alkali metal content of 1.20 mass% or less. The magnesium silicate compound according to the present disclosure has a solid acid content of 0.70 mmol / g or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel adsorbent used for adsorbing adsorbates such as alkali metals. [Background technology]

[0002] Chemical products may contain trace amounts of impurities such as catalysts used in synthesis, unreacted raw materials, and by-products produced during reactions. From the viewpoint of improving product quality, it is required to efficiently remove these impurities. Examples of methods for removing such impurities include methods for removing impurities by neutralization, distillation, extraction, or adsorption during the production process of chemical products. Among these, the adsorption method, particularly the method using an adsorbent, is often used as a simple method.

[0003] For example, polyurethane foam is produced by polymerizing raw materials, polyol and isocyanate. Polyols used in the production of polyurethane foam include polyether polyol, polymer polyol, polyester polyol, etc., and are used in any combination according to the performance of the targeted polyurethane. For example, polyether polyol is produced by addition polymerization of propylene oxide to glycerin in the presence of an alkali metal-containing basic catalyst, and a purity close to zero residual catalyst after purification is required.

[0004] In order to achieve such a high level of purity, an adsorbent capable of adsorbing and removing an alkali metal-containing basic catalyst is used in the production of polyether polyol. The adsorbent used here is usually a synthetic product such as molecular sieve, activated alumina, synthetic magnesium silicate, synthetic aluminum silicate, activated carbon, etc.; a natural product; a processed product of a natural product such as acid clay, activated clay, etc., but is not particularly limited. For example, Patent Document 1 discloses an adsorbent that can adsorb and remove an alkali metal-containing basic catalyst, which is made of an amorphous synthetic hydrous magnesium silicate compound, and has a chemical formula, BET specific surface area, alkali metal content, and average particle size each within a specific range. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2004-75674 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, these conventional adsorbents require a large amount of adsorbent relative to the adsorbent containing alkali metal, which is the adsorbent, and this leads to problems such as a decrease in yield due to the adsorption of polyether polyol by the adsorbent and a large amount of waste generated after purification.In order to solve these problems, it is strongly required to improve the adsorption capacity of the adsorbent and reduce the amount of adsorbent used.

[0007] Therefore, an object of the present invention is to provide a novel adsorbent which has a high adsorption capacity and is capable of adsorbing an adsorbate with a small amount of use. [Means for solving the problem]

[0008] As a result of intensive research conducted by the present inventors in order to achieve the above object, it has been found that by using an amorphous magnesium silicate compound having a low alkali metal content and high solid acidity as an adsorbent, it is possible to obtain a high-temperature-resistant ion exchange membrane. + , Na+ , Ni + It has been found that the adsorption ability for metal ions such as fluorine-containing fluoride is improved. The present disclosure has been completed based on this finding, and includes the following aspects.

[0009] (First Disclosure) The first disclosure is an adsorbent comprising an amorphous magnesium silicate compound. The magnesium silicate compound has an alkali metal content of 1.20 mass% or less. The magnesium silicate compound has a solid acidity of 0.70 mmol / g or more.

[0010] (Second Disclosure) The present second disclosure relates to the first disclosure, wherein the magnesium silicate compound is a compound represented by the following formula (1). (MgO) x SiO2 mH2O (1) [In formula (1), x is a number that satisfies 0.1≦x≦0.5. m is a number that satisfies 0.1≦m≦1.5.]

[0011] (Third Disclosure) The present third disclosure relates to the first or second disclosure, and more particularly to a magnesium silicate compound having a BET specific surface area of ​​200 m 2 / g~1000m 2 / g.

[0012] (Fourth Disclosure) The present fourth disclosure relates to any one of the first to third disclosures, wherein the total pore volume of the magnesium silicate compound is 0.40 cm 3 / g~1.50cm 3 / g.

[0013] (Fifth Disclosure) The fifth disclosure is a method for reducing the alkali metal content in a polyether polyol. The method includes contacting a polyether polyol containing an alkali metal-containing basic catalyst with any one of the adsorbents according to the first to fourth disclosures. Effect of the Invention

[0014] According to the present invention, it is possible to provide a novel adsorbent which has a high adsorption capacity and is capable of adsorbing an adsorbate with a small amount of use. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a powder X-ray diffraction diagram of the magnesium silicate compound of Example 2. [Diagram 2] FIG. 2 is a powder X-ray diffraction diagram of the magnesium silicate compound of Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, preferred embodiments of the adsorbent of the present invention will be described in detail. In this specification, various numerical ranges include the upper and lower limit values ​​unless otherwise specified.

[0017] [Adsorbent] The adsorbent according to one embodiment of the present invention is made of an amorphous magnesium silicate compound. The magnesium silicate compound has an alkali metal content of 1.20 mass% or less. Furthermore, the magnesium silicate compound has a solid acidity of 0.70 mmol / g or more.

[0018] The adsorbent of the present embodiment is made of an amorphous magnesium silicate compound having a low alkali metal content and high solid acidity as described above, and thus has a high K + , Na + , Ni +It can exhibit excellent adsorption ability for metal ions such as . Since its adsorption ability is much higher than that of conventional adsorbents made of magnesium silicate compounds, the adsorbent of the present embodiment can be used in a significantly reduced amount compared to such conventional adsorbents. That is, the adsorbent of the present embodiment is a novel adsorbent that has a much higher adsorption ability than conventional adsorbents made of magnesium silicate compounds and can adsorb the adsorbate with a small amount of use. Furthermore, the adsorbent of the present embodiment has the advantage of being able to contribute to the reduction of energy consumption and waste disposal, and can contribute to the achievement of the SDGs (Sustainable Development Goals) adopted at the United Nations Summit.

[0019] (Magnesium silicate compound) As described above, the adsorbent according to one embodiment of the present invention is made of an amorphous magnesium silicate compound. Here, the term "amorphous magnesium silicate compound" refers to a magnesium silicate compound whose powder X-ray diffraction pattern shows an amorphous form.

[0020] (Alkali metal content) In this embodiment, the alkali metal content of the magnesium silicate compound is 1.20 mass % or less.

[0021] The alkali metal content of such a specific amount or less can be obtained, for example, by adjusting the pH of the reaction slurry to be low during the synthesis of the magnesium silicate compound described below, or by carrying out a heat aging treatment and / or an acid treatment after the synthesis. For example, the alkali metal content can be reduced by lowering the pH of the reaction slurry during the synthesis of the magnesium silicate compound. In addition, it is considered that the alkali metal content can be reduced by carrying out a heat aging treatment after the synthesis of the magnesium silicate compound, as the dissolution and precipitation of the magnesium silicate compound is promoted. In addition, when an acid treatment is carried out after the synthesis of the magnesium silicate compound, the alkali metal component contained therein is replaced with an acid proton, so that the alkali metal content can be reduced.

[0022] In this specification, the alkali metal component refers to an alkali metal such as sodium or potassium derived from the raw material.

[0023] The alkali metal content of the magnesium silicate compound is preferably 1.10% by mass or less, more preferably 1.00% by mass or less. The lower limit of the alkali metal content of the magnesium silicate compound is not particularly limited, but may be, for example, 0.001% by mass.

[0024] (Solid acid amount) In one embodiment of the present invention, the magnesium silicate compound has a solid acidity of 0.70 mmol / g or more.

[0025] Such a specific amount or more of solid acidity can be obtained by the same means as the alkali metal content described above. That is, such a specific amount or more of solid acidity can be obtained, for example, by adjusting the pH of the reaction slurry to be low during the synthesis of the magnesium silicate compound described later, or by carrying out a heat aging treatment and / or an acid treatment after the synthesis. For example, by lowering the pH of the reaction slurry during the synthesis of the magnesium silicate compound, the alkali metal content can be reduced and the solid acidity can be increased. In addition, when a heat aging treatment is carried out after the synthesis of the magnesium silicate compound, it is considered that the dissolution and precipitation of the magnesium silicate compound is promoted, thereby reducing the alkali metal content and increasing the solid acidity. In addition, when an acid treatment is carried out after the synthesis of the magnesium silicate compound, the alkali metal component contained therein is replaced with the proton of the acid, so that the alkali metal content can be reduced and the solid acidity can be increased.

[0026] The solid acid amount of the magnesium silicate compound is preferably 1.00 mmol / g or more, more preferably 1.50 mmol / g or more. The upper limit of the solid acid amount of the magnesium silicate compound is not particularly limited, but may be, for example, 10.00 mmol / g.

[0027] A specific method for measuring the solid acidity will be described in the Examples below.

[0028] In this way, the magnesium silicate compound in one embodiment of the present invention has an alkali metal content equal to or less than the specific amount and a high solid acid content equal to or more than the specific amount, and thus exhibits an extremely excellent adsorption ability for various metal ions, and thus the adsorbent of this embodiment can adsorb various metal ions in a smaller amount than adsorbents made of conventional magnesium silicate compounds.

[0029] (chemical formula) In this embodiment, the magnesium silicate compound is not particularly limited except that it is amorphous, has an alkali metal content of not more than the specific amount, and has a high solid acidity of not less than the specific amount, but is preferably a hydrous magnesium silicate compound represented by the following formula (1): (MgO) x SiO2 mH2O (1) [In formula (1), x is a number that satisfies 0.1≦x≦0.5. m is a number that satisfies 0.1≦m≦1.5.]

[0030] When the magnesium silicate compound is a hydrous magnesium silicate compound represented by the formula (1), it can more reliably exhibit the excellent adsorption ability for metal ions described above.

[0031] In the above formula (1), the preferable range of x is 0.2≦x≦0.35.

[0032] (BET specific surface area) In this embodiment, the magnesium silicate compound has a BET specific surface area of ​​200 m 2 / g~1000m 2 When the BET specific surface area of ​​the magnesium silicate compound is within this range, a certain amount of adsorption can be ensured, and therefore the excellent adsorption ability for the above-mentioned metal ions can be more reliably exhibited.

[0033] The BET specific surface area of ​​magnesium silicate compound is 220m 2 / g or more is more preferable, and 250m 2 The BET specific surface area of ​​the magnesium silicate compound is preferably 900 m 2 / g or less is more preferable, and 2 It is more preferable that the molecular weight is not more than 1 / g.

[0034] In this specification, the BET specific surface area means the specific surface area of ​​a magnesium silicate compound measured by the BET method. A specific method for measuring the BET specific surface area will be described in the Examples below.

[0035] (total pore volume) In this embodiment, the total pore volume of the magnesium silicate compound is 0.40 cm 3 / g~1.50cm 3 When the total pore volume of the magnesium silicate compound is within this range, a certain amount of adsorption can be ensured, and therefore the excellent adsorption ability for the above-mentioned metal ions can be more reliably exhibited.

[0036] The total pore volume of the magnesium silicate compound is 0.50 cm 3 / g or more. The total pore volume of the magnesium silicate compound is preferably 1.20 cm 3 It is more preferable that the molecular weight is not more than 1 / g.

[0037] A specific method for measuring the total pore volume will be described in the Examples below.

[0038] (Average particle size) In this embodiment, the magnesium silicate compound preferably has an average particle size of 2.0 μm to 60.0 μm. When the average particle size of the magnesium silicate compound is within this range, the specific surface area can be increased and a certain amount of adsorption can be secured, so that the excellent adsorption ability for the above-mentioned metal ions can be more reliably exhibited.

[0039] The average particle size of the magnesium silicate compound is more preferably 5.0 μm or more, and more preferably 50.0 μm or less.

[0040] The specific method for measuring the average particle size will be described later in the Examples section.

[0041] [Manufacturing method] The method for producing the magnesium silicate compound constituting the adsorbent according to one embodiment of the present invention will be described below by taking the above-mentioned method for producing the hydrous magnesium silicate compound as an example. Note that the magnesium silicate compound that can be used as the adsorbent of the present invention is amorphous, has an alkali metal content of the above-mentioned specific amount or less, and has a high solid acidity of the above-mentioned specific amount or more, so long as it is not limited in any way in its production method or conditions.

[0042] (synthesis process) The above-mentioned hydrous magnesium silicate compound can be synthesized by reacting a water-soluble magnesium compound with a water-soluble silicic acid compound. Examples of the water-soluble magnesium compound include magnesium chloride, magnesium sulfate, and magnesium nitrate. Examples of the water-soluble silicic acid compound include sodium silicate, commonly known as water glass, represented by the general formula Na2O·nSiO2 (n=2-4); sodium metasilicate; sodium orthosilicate; and alkali silicates such as potassium silicate. Of these, it is preferable to use No. 3 water glass as the water-soluble silicic acid compound.

[0043] The reaction may be a batch reaction in which a certain amount of an aqueous solution of a magnesium compound and a certain amount of an aqueous solution of a silicic acid compound are simultaneously poured into a reaction tank, or a continuous reaction in which a certain amount of an aqueous solution of a magnesium compound and a certain amount of an aqueous solution of a silicic acid compound are continuously poured into a reaction tank to continuously obtain a reaction slurry. A continuous reaction is advantageous in terms of production efficiency.

[0044] The reaction temperature is not particularly limited, and may be, for example, a temperature of 15° C. to 60° C. For example, the reaction may be carried out by placing the reaction tank in a thermostatic bath controlled at a constant temperature, or a container containing an aqueous magnesium compound solution and a container containing an aqueous silicic acid compound solution may be placed in a thermostatic bath controlled at a constant temperature, and the aqueous solution may be poured from each container to the reaction tank using a metering pump.

[0045] The reaction pH is, for example, 7 to 10, and preferably 8.5 to 9.5. By adjusting the reaction pH within this range, the primary particles of the synthesized magnesium silicate hydrous compound can be made into fine particles. By making the primary particles into fine particles, the specific surface area of ​​the magnesium silicate hydrous compound can be increased, and the adsorption sites can be increased, thereby improving the adsorption capacity.

[0046] (heat aging process) The reaction slurry obtained by the synthesis step may be aged by heating and stirring. The aging temperature is, for example, 60°C to 120°C, preferably 70°C to 110°C, and more preferably 80°C to 100°C. The aging time is, for example, 0.5 hours to 18 hours, preferably 1 hour to 12 hours, and more preferably 2 hours to 6 hours. By heating and aging the synthesized hydrous magnesium silicate compound under such specific conditions, the specific surface area of ​​the hydrous magnesium silicate compound is increased, and the adsorption sites are increased, thereby improving the adsorption capacity.

[0047] (Acid treatment process) The hydrous magnesium silicate compound after synthesis may be acid-treated using an inorganic acid. By carrying out such acid treatment, the alkali metal component in the hydrous magnesium silicate compound after synthesis is replaced with a proton of the inorganic acid, and the solid acidity of the hydrous magnesium silicate compound is increased, so that the adsorption capacity of the alkali metal ion can be improved. The alkali metal component is, for example, sodium or potassium derived from the raw material.

[0048] The inorganic acid that can be used in the acid treatment step is not particularly limited, but examples thereof include sulfuric acid, hydrochloric acid, and nitric acid.

[0049] A specific method for the acid treatment step, that is, a specific method for replacing the alkali metal component in the hydrous magnesium silicate compound after synthesis with a proton of an inorganic acid, may, for example, be a method of separating the reaction slurry into solid and liquid, washing the solid matter with diluted inorganic acid, and then washing with water.Another method may be a method of separating the reaction slurry into solid and liquid, suspending the solid matter in diluted inorganic acid and stirring for a certain period of time, dehydrating, and then washing with water.

[0050] The concentration of the inorganic acid is, for example, 0.01 mol / L to 0.5 mol / L, preferably 0.02 mol / L to 0.2 mol / L. When the concentration of the diluted inorganic acid is 0.01 mol / L or more, the protons in the inorganic acid are sufficiently replaced with alkali metal components. On the other hand, when the concentration of the diluted inorganic acid is 0.5 mol / L or less, sulfate ions, chloride ions, nitrate ions, etc. of the inorganic acid are less likely to remain as impurities in the solid matter. In addition, when the concentration of the diluted inorganic acid is 0.5 mol / L or less, magnesium in magnesium silicate is less likely to be dissolved by the inorganic acid.

[0051] (drying process) The drying method of the hydrous magnesium silicate compound after synthesis is not particularly limited, but for example, a shelf drying method in which the dehydrated solid is placed in a stainless steel tray and dried with hot air can be mentioned. Other drying methods include a spray drying method in which the dehydrated solid is slurried to a concentration of 100 g / L to 500 g / L in terms of solid content, and then treated with a wet grinder such as a ball mill, colloid mill, SC mill, or Dyno mill to adjust the shape of the dried product, and then dried with a spray dryer. The spray drying method is preferably used as the drying method because it is easy to granulate the hydrous magnesium silicate compound into a spherical shape. Granulating the hydrous magnesium silicate compound into a spherical shape has the advantage of making it easy to separate and remove after the adsorption treatment.

[0052] The magnesium silicate compound obtained by the above-mentioned production method is amorphous and has an alkali metal content of not more than the above-mentioned specific amount and a high solid acidity of not less than the above-mentioned specific amount due to the reaction conditions during synthesis and the heat aging step and / or acid treatment step after synthesis.

[0053] Such magnesium silicate compounds can be used, for example, as adsorbents for various industrial applications, but as described above, they are particularly useful as adsorbents for adsorbing and removing alkali metal-containing basic catalysts during the production of polyether polyols.

[0054] [Method for reducing alkali metal content in polyether polyol] Another embodiment of the present invention is a method for reducing the alkali metal content in a polyether polyol, comprising contacting a polyether polyol containing an alkali metal-containing basic catalyst with an adsorbent comprising an amorphous magnesium silicate compound having an alkali metal content equal to or less than the specific amount and a high solid acidity equal to or more than the specific amount.

[0055] As described above, this reduction method uses an adsorbent with an extremely excellent adsorption capacity that can adsorb various metal ions with a small amount of the adsorbent used, so that the yield of polyether polyol can be increased and the amount of waste generated after purification can be reduced.

[0056] A specific method for adsorbing and removing the residual alkali metal-containing basic catalyst contained in the polyether polyol includes, for example, a method in which the above-mentioned magnesium silicate compound is added as an adsorbent to the polyether polyol, the mixture is mixed, and then the adsorbent is separated and removed.

[0057] The amount of adsorbent added depends on the amount of the remaining alkali metal-containing basic catalyst, but is, for example, 0.1 to 10.0% by mass, and preferably 0.5 to 5.0% by mass, based on the mass of the polyether polyol.

[0058] The adsorption treatment can be performed, for example, under stirring at a treatment temperature of 70°C to 150°C for a treatment time of 5 to 120 minutes. Water may be added during the adsorption treatment. In this case, it is preferable to add 0.5% by mass to 3.0% by mass of water based on the mass of the polyether polyol. Note that an antioxidant may be added to the polyether polyol before the adsorption treatment to prevent deterioration.

[0059] In addition, before adding the adsorbent to the polyether polyol, at least one of inorganic acids such as phosphoric acid, sulfuric acid, sodium hydrogen pyrophosphate, and oxalic acid, inorganic acid salts, and organic acids may be added to cause a neutralization reaction. In this case, the adsorbent is added after the neutralization reaction is completed.

[0060] The present invention is not limited to the above-described embodiments or the examples described below, and appropriate combinations, substitutions, modifications, and the like are possible within the scope that does not deviate from the purpose and intent of the present invention. EXAMPLES

[0061] Hereinafter, the present invention will be described more specifically by way of examples and comparative examples, but the present invention is not limited only to these examples.

[0062] The measurement methods for various physical properties and the like regarding the examples and comparative examples are as follows.

[0063] <SiO2 / MgO molar ratio and alkali metal content> The SiO2 / MgO molar ratio and alkali metal content of the magnesium silicate compound were measured using a scanning fluorescence X-ray analyzer "ZSX Primus IV" manufactured by Rigaku Corporation.

[0064] <BET specific surface area and total pore volume> The BET specific surface area and total pore volume of the magnesium silicate compound were measured using a high-precision critical surface area and pore distribution measuring device "BELsorp-max" manufactured by MicrotracBEL Corporation.

[0065] <Liquid pH> The liquid pH of the magnesium silicate compound was measured as follows. 2.0 g of the dried magnesium silicate compound and 40 mL of ion-exchanged water were placed in a beaker and stirred with a magnetic stirrer for 5 minutes, and then filtered using a No. 5C filter paper, and the pH of the filtrate was measured. The pH of this filtrate was taken as the liquid pH of the magnesium silicate compound.

[0066] <Solid acid amount> 0.1 g of dried magnesium silicate compound was placed in a stoppered Erlenmeyer flask, and 5 mL of benzene (Wako Chemical Special Grade) was added. 1 mL of 0.1 wt% methyl orange benzene solution was added as an indicator with pKa = 4.8 to color the dried particles red. The dried particles were titrated with 0.1 mol / L n-butylamine-benzene solution until they turned yellow, and the amount of n-butylamine-benzene solution required for the titration was A (mL). When the Erlenmeyer flask was stoppered and left to stand for 24 hours, the dried particles returned to red, so they were titrated again with 0.1 mol / L n-butylamine-benzene solution until they turned yellow, and the amount of n-butylamine-benzene solution required for the titration was B (mL). This operation was repeated once more, and the amount of n-butylamine-benzene solution required for the titration was C (mL). The amount of solid acid was calculated from the total amount of titration for three times based on the following formula. Solid acid amount (mmol / g)=0.1(A+B+C) / 0.1g

[0067] <Average particle size> The average particle size of the magnesium silicate compound was measured using a particle size distribution measuring device "MICROTRAC MT3000II series" manufactured by Nikkiso Co., Ltd. Specifically, first, 70 mL of 2.0 g / L sodium hexametaphosphate aqueous solution was added to 0.7 g of dried magnesium silicate compound, and stirred with a magnetic stirrer. 2 to 4 mL of the dispersion was added to a 2.0 g / L sodium hexametaphosphate aqueous solution, and the dispersion was circulated for 1 minute, after which the particle size distribution was measured using the particle size distribution measuring device. The average particle size was calculated from the obtained 50% cumulative (median diameter).

[0068] Next, examples of the present invention and comparative examples will be described.

[0069] Example 1 (Synthesis Test) A 1.17 mol / L magnesium sulfate aqueous solution and a No. 3 water glass aqueous solution consisting of 0.46 mol / L Na2O and 1.44 mol / L SiO2 were continuously poured into a continuous reaction tank at a constant amount to cause a coprecipitation reaction. The reaction temperature was 40°C. The pH of the resulting reaction slurry was 8.9. The average particle size of the reaction product particles was 8.2 μm. The reaction slurry was then dehydrated by suction filtration using a Nutsche filter, and the solid matter was washed with ion-exchanged water in an amount 20 times the weight of the solid matter. The resulting solid matter was slurried to a concentration of 250 g / L and spray-dried using a spray dryer.

[0070] The dried magnesium silicate compound of Example 1 thus obtained was subjected to various physical properties measurements. As a result, the SiO2 / MgO molar ratio of the magnesium silicate compound of Example 1 was 3.5. The alkali metal content of the magnesium silicate compound of Example 1 was 1.00 mass%. The BET specific surface area of ​​the magnesium silicate compound of Example 1 was 295 m 2 The total pore volume of the magnesium silicate compound of Example 1 was 0.47 cm 3 / g. Furthermore, the liquid pH of the magnesium silicate compound of Example 1 was 9.8. The solid acid amount of the magnesium silicate compound of Example 1 was 0.73 mmol / g. The average particle size of the magnesium silicate compound of Example 1 was 42.2 μm. Furthermore, the powder method X-ray diffraction diagram of the magnesium silicate compound of Example 1 showed that it was amorphous.

[0071] (Adsorption test 1) 160 g of polypropylene glycol (degree of polymerization: 3,000) in which potassium hydroxide had been dissolved to a potassium concentration of 1400 ppm was placed in a four-necked round-bottom flask and heated and stirred with a mantle heater while replacing with nitrogen. When the liquid temperature reached 85°C, 1.6 mL of ion-exchanged water was added, and then, when the liquid temperature reached 90°C, 0.4 g of an adsorbent made of a synthesized magnesium silicate compound was added, and the mixture was heated and stirred for 30 minutes. After 30 minutes, the treated liquid was immediately suction-filtered with a suction pressure of 0.02 MPa to obtain a filtrate. The filtrate was subjected to potentiometric titration with 0.01 N hydrochloric acid to determine the potassium concentration in the filtrate, which was 209 ppm.

[0072] (Adsorption test 2) 160 g of polypropylene glycol (degree of polymerization: 3,000) in which potassium hydroxide had been dissolved in advance so that the potassium concentration was 1400 ppm was placed in a four-necked round-bottom flask, and heated and stirred with a mantle heater while replacing with nitrogen. When the liquid temperature reached 85°C, 1.6 mL of ion-exchanged water was added, and then, when the liquid temperature reached 90°C, 0.56 g of an adsorbent made of a synthesized magnesium silicate compound was added, and the mixture was heated and stirred for 30 minutes. After 30 minutes, the treated liquid was immediately suction-filtered with a suction pressure of 0.02 MPa to obtain a filtrate. The filtrate was subjected to potentiometric titration with 0.01 N hydrochloric acid to determine the potassium concentration in the filtrate, which was 128 ppm.

[0073] (Adsorption test 3) 160 g of polypropylene glycol (degree of polymerization: 3,000) in which potassium hydroxide had been dissolved in advance to give a potassium concentration of 1400 ppm was placed in a four-necked round-bottom flask and heated and stirred with a mantle heater while replacing with nitrogen. When the liquid temperature reached 85°C, 1.6 mL of ion-exchanged water was added, and then, when the liquid temperature reached 90°C, 0.8 g of an adsorbent made of a synthesized magnesium silicate compound was added, and the mixture was heated and stirred for 30 minutes. After 30 minutes, the treated liquid was immediately suction-filtered with a suction pressure of 0.02 MPa to obtain a filtrate. The filtrate was subjected to potentiometric titration with 0.01 N hydrochloric acid to determine the potassium concentration in the filtrate, which was 38 ppm.

[0074] Example 2 (Synthesis Test) A 1.17 mol / L magnesium sulfate aqueous solution and a No. 3 water glass aqueous solution consisting of 0.46 mol / L Na2O and 1.44 mol / L SiO2 were continuously poured into a continuous reaction tank at a constant amount to cause a coprecipitation reaction. The reaction temperature was 40°C. The pH of the resulting reaction slurry was 8.9. The average particle size of the reaction product particles was 8.2 μm. The reaction slurry was then dehydrated by suction filtration using a Nutsche filter, and the solid matter was washed with 0.05 mol / L sulfuric acid in an amount 15 times the weight of the solid matter, and the sodium in the solid matter was ion-exchanged, followed by washing with 20 times the amount of ion-exchanged water. The resulting solid matter was slurried to a concentration of 250 g / L and spray-dried using a spray dryer.

[0075] The dried magnesium silicate compound of Example 2 thus obtained was subjected to various physical properties measurements. As a result, the SiO2 / MgO molar ratio of the magnesium silicate compound of Example 2 was 3.9. The alkali metal content of the magnesium silicate compound of Example 2 was 0.17 mass%. The BET specific surface area of ​​the magnesium silicate compound of Example 2 was 259 m 2 The total pore volume of the magnesium silicate compound of Example 2 was 0.56 cm 3 / g. Furthermore, the liquid pH of the magnesium silicate compound of Example 2 was 9.1. The solid acid amount of the magnesium silicate compound of Example 2 was 0.90 mmol / g. The average particle size of the magnesium silicate compound of Example 2 was 43.8 μm. Furthermore, the powder method X-ray diffraction diagram of the magnesium silicate compound of Example 2 showed that it was amorphous as shown in FIG. 1.

[0076] (Adsorption test 1) When an adsorption test was carried out in exactly the same manner as in Adsorption Test 1 of Example 1, the potassium concentration in the filtrate was 211 ppm.

[0077] (Adsorption test 2) When an adsorption test was carried out in exactly the same manner as in Adsorption Test 2 of Example 1, the potassium concentration in the filtrate was 104 ppm.

[0078] (Adsorption test 3) When an adsorption test was carried out in exactly the same manner as in Adsorption Test 3 of Example 1, the potassium concentration in the filtrate was 34 ppm.

[0079] Example 3 (Synthesis Test) A 1.17 mol / L magnesium sulfate aqueous solution and a No. 3 water glass aqueous solution consisting of 0.46 mol / L Na2O and 1.44 mol / L SiO2 were continuously poured into a continuous reaction tank at a constant amount to cause a coprecipitation reaction. The reaction temperature was 40°C. The pH of the resulting reaction slurry was 8.9. The average particle size of the reaction product particles was 8.2 μm. The reaction slurry was heated and stirred at 90°C for 2 hours. After that, the slurry was suction filtered with a Nutsche filter and dehydrated, and the solid matter was washed with ion-exchanged water in an amount 20 times the weight of the solid matter. The resulting solid matter was slurried to a concentration of 250 g / L and spray-dried with a spray dryer.

[0080] The dried magnesium silicate compound of Example 3 thus obtained was subjected to various physical properties measurements. As a result, the SiO2 / MgO molar ratio of the magnesium silicate compound of Example 3 was 3.4. The alkali metal content of the magnesium silicate compound of Example 3 was 0.98 mass%. The BET specific surface area of ​​the magnesium silicate compound of Example 3 was 714 m 2 The total pore volume of the magnesium silicate compound of Example 3 was 1.05 cm 3 / g. Furthermore, the liquid pH of the magnesium silicate compound of Example 3 was 9.6. The solid acid amount of the magnesium silicate compound of Example 3 was 1.65 mmol / g. The average particle size of the magnesium silicate compound of Example 3 was 39.8 μm. Furthermore, the powder method X-ray diffraction diagram of the magnesium silicate compound of Example 3 showed that it was amorphous.

[0081] (Adsorption test 1) When an adsorption test was carried out in exactly the same manner as in Adsorption Test 1 of Example 1, the potassium concentration in the filtrate was 123 ppm.

[0082] (Adsorption test 2) When an adsorption test was carried out in exactly the same manner as in Adsorption Test 2 of Example 1, the potassium concentration in the filtrate was 70 ppm.

[0083] (Adsorption test 3) When an adsorption test was carried out in exactly the same manner as in Adsorption Test 3 of Example 1, the potassium concentration in the filtrate was 40 ppm.

[0084] Example 4 (Synthesis Test) A 1.17 mol / L magnesium sulfate aqueous solution and a No. 3 water glass aqueous solution consisting of 0.46 mol / L Na2O and 1.44 mol / L SiO2 were continuously poured into a continuous reaction tank at a constant amount to cause a coprecipitation reaction. The reaction temperature was 40°C. The pH of the resulting reaction slurry was 8.9. The average particle size of the reaction product particles was 8.2 μm. Furthermore, the reaction slurry was heated and stirred at 90°C for 2 hours. Thereafter, the slurry was suction filtered with a Nutsche filter to dehydrate it, and the solid was washed with 0.05 mol / L sulfuric acid in an amount 15 times the weight of the solid, and the sodium in the solid was ion-exchanged, and then similarly washed with 20 times the amount of ion-exchanged water. The resulting solid was slurried to a concentration of 250 g / L and spray-dried with a spray dryer.

[0085] The dried magnesium silicate compound of Example 4 thus obtained was subjected to various physical properties measurements. As a result, the SiO2 / MgO molar ratio of the magnesium silicate compound of Example 4 was 4.0. The alkali metal content of the magnesium silicate compound of Example 4 was 0.08 mass%. The BET specific surface area of ​​the magnesium silicate compound of Example 4 was 702 m 2 The total pore volume of the magnesium silicate compound of Example 4 was 1.07 cm 3 / g. Furthermore, the liquid pH of the magnesium silicate compound of Example 4 was 8.4. The solid acid amount of the magnesium silicate compound of Example 4 was 1.62 mmol / g. The average particle size of the magnesium silicate compound of Example 4 was 39.8 μm. Furthermore, the powder method X-ray diffraction diagram of the magnesium silicate compound of Example 4 showed that it was amorphous as shown in FIG. 2.

[0086] (Adsorption test 1) When an adsorption test was carried out in exactly the same manner as in Adsorption Test 1 of Example 1, the potassium concentration in the filtrate was 162 ppm.

[0087] (Adsorption test 2) When an adsorption test was carried out in exactly the same manner as in Adsorption Test 2 of Example 1, the potassium concentration in the filtrate was 78 ppm.

[0088] (Adsorption test 3) When an adsorption test was carried out in exactly the same manner as in Adsorption Test 3 of Example 1, the potassium concentration in the filtrate was 33 ppm.

[0089] Comparative Example 1 (Synthesis Test) A 1.35 mol / L magnesium sulfate aqueous solution and a No. 3 water glass aqueous solution consisting of 0.55 mol / L Na2O and 1.73 mol / L SiO2 were continuously poured into a continuous reaction tank at a constant amount to cause a coprecipitation reaction. The reaction temperature was 40°C. The pH of the resulting reaction slurry was 9.3. The average particle size of the reaction product particles was 12.8 μm. The reaction slurry was then dehydrated by suction filtration using a Nutsche filter, and the solid matter was washed with ion-exchanged water in an amount 20 times the weight of the solid matter. The resulting solid matter was slurried to a concentration of 250 g / L and spray-dried using a spray dryer.

[0090] The dried magnesium silicate compound of Comparative Example 1 thus obtained was subjected to various physical properties measurements. As a result, the SiO2 / MgO molar ratio of the magnesium silicate compound of Comparative Example 1 was 3.6. The alkali metal content of the magnesium silicate compound of Comparative Example 1 was 1.60 mass%. The BET specific surface area of ​​the magnesium silicate compound of Comparative Example 1 was 126 m 2 The total pore volume of the magnesium silicate compound of Comparative Example 1 was 0.24 cm 3 / g. Furthermore, the liquid pH of the magnesium silicate compound of Comparative Example 1 was 10.1. The solid acid amount of the magnesium silicate compound of Comparative Example 1 was 0.61 mmol / g. The average particle size of the magnesium silicate compound of Comparative Example 1 was 40.6 μm. Furthermore, the powder method X-ray diffraction diagram of the magnesium silicate compound of Comparative Example 1 showed that it was amorphous.

[0091] (Adsorption test 1) When an adsorption test was carried out in exactly the same manner as in Adsorption Test 1 of Example 1, the potassium concentration in the filtrate was 424 ppm.

[0092] (Adsorption test 2) When an adsorption test was carried out in exactly the same manner as in Adsorption Test 2 of Example 1, the potassium concentration in the filtrate was 283 ppm.

[0093] (Adsorption test 3) When an adsorption test was carried out in exactly the same manner as in Adsorption Test 3 of Example 1, the potassium concentration in the filtrate was 65 ppm.

[0094] The measurement results of various physical properties of each of the magnesium silicate compounds of Examples 1 to 4 and Comparative Example 1 are shown in the following Table 1. In addition, the potassium concentration in the filtrate in the adsorption test is represented as "residual K amount" in Table 1.

[0095] [Table 1]

[0096] As shown in Table 1, the adsorbents made of the magnesium silicate compounds of Examples 1 to 4 had a small amount of residual K in the adsorption test, and were found to exhibit extremely excellent adsorption performance for alkali metals. On the other hand, the adsorbent made of the magnesium silicate compound of Comparative Example 1 had a large amount of residual K in the adsorption test, and was found to have insufficient adsorption performance for alkali metals. [Industrial Applicability]

[0097] The adsorbent of the present invention has a much higher adsorption capacity than conventional adsorbents made of magnesium silicate compounds, and can adsorb adsorbents with a small amount of use, so it can be suitably used, for example, as an adsorbent for various industrial applications. The adsorbent of the present invention is particularly useful as an adsorbent for adsorbing and removing an alkali metal-containing basic catalyst when producing polyether polyol.

Claims

1. An amorphous magnesium silicate compound, The magnesium silicate compound is The alkali metal content is 1.20% by mass or less, The solid acid amount is 0.70 mmol / g or more, BET specific surface area is 200m 2 / g to 1000m 2 / g, A compound represented by the following formula (1): (MgO) x ・SiO 2 ・mH 2 O ・・・(1) [In formula (1), x is a number satisfying 0.1≦x≦0.5, and m is a number satisfying 0.1≦m≦1.5.]

2. The total pore volume of the magnesium silicate compound is 0.40 cm 3 / g ~ 1.50 cm 3 The compound according to claim 1, wherein the molecular weight is 1.0 to 1.0 g.

3. 2. The compound according to claim 1, wherein the average particle size of the magnesium silicate compound is from 2.0 μm to 60.0 μm.

Citation Information

Patent Citations

  • Method for purifying polyoxyalkylenepolyol

    JP1991195728A

  • Purification of polyether

    JP1995258403A

  • Polyoxyalkylene polyol and process for producing the same

    JP2001261813A

  • Method for purifying crude polyether and adsorbent

    JP2004075674A

  • Purification of crude polyalkylene oxide polymers using acid-functionalized silica and metal silicates

    JP2020513048A